2012
DOI: 10.1159/000338649
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Dilemma in a Patient with Jaundice: How to Differentiate between Autoimmune Pancreatitis, Primary Sclerosing Cholangitis and Pancreas Carcinoma

Abstract: A 68-year-old male patient was referred to our institution in May 2011 for a suspected tumor in the pancreatic head with consecutive jaundice. Using magnetic resonance imaging, further differentiation between chronic inflammation and a malignant process was not possible with certainty. Apart from cholestasis, laboratory studies showed increased values for CA 19-9 to 532 U/ml (normal <37 U/ml) and hypergammaglobulinemia (immunoglobulin G, IgG) of 19.3% (normal 8.0–15.8%) with an elevation of the IgG4 subtype to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although there is a general agreement that steroids are the ideal initial treatment, no clear consensus regarding treatment for disease relapse exists. According to actual literature, readministration of steroid pulse therapy or addition of immunomodulators such as thiopurine, mycophenolate, rituximab, or tacrolimus is recommended [ 5 , 6 , 12 , 36 , 41 43 ]. An international multicenter analysis revealed that risk for relapse is higher in AIP1 than in AIP2 patients (31% versus 9%) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a general agreement that steroids are the ideal initial treatment, no clear consensus regarding treatment for disease relapse exists. According to actual literature, readministration of steroid pulse therapy or addition of immunomodulators such as thiopurine, mycophenolate, rituximab, or tacrolimus is recommended [ 5 , 6 , 12 , 36 , 41 43 ]. An international multicenter analysis revealed that risk for relapse is higher in AIP1 than in AIP2 patients (31% versus 9%) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 30% of patients undergoing surgery for initially suspected pancreatic cancer turned out as benign pancreatic disease afterwards. Therefore, serological markers such as high IgG4 and CA 19-9 levels as well as the presence of carbonic anhydrase-II antibodies might be helpful diagnostic tools [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both types of AIP require integration of clinical, radiological, biochemical and pathological findings to diagnose. Part of the difficulty is that AIP shares similar clinical and radiological manifestations with tumours, especially adenocarcinoma 1,2,17,18,19,21 . Different clinical and radiological modalities, including serum IgG4, CA19‐9, tumour‐specific antigens, gene expression, endoscopic ultrasonography, computerised tomography (CT) and magnetic resonance imaging (MRI), have been explored for differentiating AIP from pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune pancreatitis (AIP) is a mimic of neoplasia in its clinical, radiological and histological features 1–7 . Current consensus divides AIP into two subtypes 2–8 .…”
Section: Introductionmentioning
confidence: 99%